Community Empowerment in Building Social Networks through the Herbal Planting Program in the Sijambur Village Community, Ronggurnihuta District, Samosir Regency - Puspitawati; Murni Eva Marlina; Rosramadhana; Zanrison Naibaho; Febrini Estomihi Lumban Raja; Reza Selvina Putri Siregar (Jurnal Pengabdian Masyarakat Bestari, 2022)
The implementation of this service was carried out in Sijambur Village, Ronggurnihuta District, Samosir Regency. If seen based on the geographical location of Sijambur Village, it is a village located in a mountainous area so that the majority of the people are farmers. In this regard, the activities of the community empowerment community partnership program in building social networks through the herbal planting program offer several alternative solutions, including: providing socialization of community empowerment in building social networks by planting herbal plants, providing assistance to the community and participating in planting plants. herbs to preserve the beauty of the natural environment around community settlements and increase the utilization of the potential of the surrounding environment. The result is the implementation of community empowerment through socialization by building a social network for the community and planting herbal plants in the environment around the community's dwelling.